Evaluation of Pivot Irrigation Systems in South Western in Libya - Shaki, Ali; Aljarmawey, Mohamed (Journal of Pure & Applied Sciences, 2023)
The Pivot irrigation system is becoming widely spread use in southern Libya in recent decades. This was limited in the past to general strategic projects that are managed by specialized companies and trained technical cadres. Now that it has become widespread in the private sector. The evaluation of these systems has become very important, especially in terms of the lack of good designs and scientific consultations when choosing these systems. This paper aimed to conduct experiments to measure the Center Pivot Distribution Uniformity in some agricultural areas in the southern region of Libya. This paper concluded that, most of the Distribution Uniformity of those systems are very poor, which ranged from 13% - 78% which considered less than what the recommended values. So they need reevaluation